Reduction of Radioactive Waste Through the Reuse and Recycle Policy of the Sealed Radioactive Sources Management - T. Marpaung (PPIKSN-BATAN, 2012)
In the past few years, the utilization of sealed source for medical, industrial and research purposes has shown an accelerating increase. This situation will lead to increases in the amount of sealed radioactive. During its use, a sealed radioactive waste will eventually become either a spent sealed source or disused sealed radioactive source (DSRS), due to certain factors. The reduction of the amount of radioactive waste can be executed through the application of reuse and recycle of sealed source. The reuse and recycle policy for spent and disused sealed sources are not already specified yet. The reuse of spent sealed sources can be applied only for the sources which had been used in the medical field for radiotherapy, namely the reuse of a teletherapy Co-60 source in a calibration facility. The recycle of a spent sealed source can be performed for radioactive sources with relatively high activities and long half-lives; however, the recycling activity may only be performed by the manufacturer. To avoid legal conflicts, in the amendment to the Government Regulation No.27 Year 2002 on Management of Radioactive Waste, there will be a recommendation for a new scheme in the management of radioactive waste to facilitate the application of the principles of reduce, reuse, and recycle.Received: 20November 2010; Revised: 11 June 2012; Accepted: 30 August 2012